2005
DOI: 10.1002/pbc.20433
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of 84 patients with nasopharyngeal carcinoma in childhood

Abstract: The cisplatin-based regimen was the best chemotherapeutic regimen. Less toxic regimens with better survival rates should be investigated in patients with nasopharyngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
30
4
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
10
30
4
3
Order By: Relevance
“…This study has also showed that clinical hypothyroidism occurred more frequently in younger patients, female sex and following conformal radiotherapy. Some reports have also suggested a higher incidence of radiationinduced hypothyroidism in the younger age group treated for Hodgkin's disease (Shalet et al, 1977) or for NPC (Zubizarreta et al, 2000), while other reports did not (Daoud et al, 2003;Kupeli et al, 2006). These rates of radiation-induced hypothyroidism are significantly higher than the reported rates of 0.3-1.3% in the general population (Wu et al, 2010).…”
Section: Radiation-induced Primary Thyroid Dysfunctioncontrasting
confidence: 52%
“…This study has also showed that clinical hypothyroidism occurred more frequently in younger patients, female sex and following conformal radiotherapy. Some reports have also suggested a higher incidence of radiationinduced hypothyroidism in the younger age group treated for Hodgkin's disease (Shalet et al, 1977) or for NPC (Zubizarreta et al, 2000), while other reports did not (Daoud et al, 2003;Kupeli et al, 2006). These rates of radiation-induced hypothyroidism are significantly higher than the reported rates of 0.3-1.3% in the general population (Wu et al, 2010).…”
Section: Radiation-induced Primary Thyroid Dysfunctioncontrasting
confidence: 52%
“…In recent years, clinical studies have demonstrated effectiveness of 5-FU on pediatric tumors, such as low-grade gliomas, nasopharyngeal carcinoma and hepatoblastoma (Casanova et al, 2012;Kupeli et al, 2006;Lee et al, 2006;Rodriguez-Galindo et al, 2005). The previous studies, including experimental and clinical reports, have suggested that 5-FU could result in oligodendrocytes (OLs) injury and reversible white-matter degeneration in adult patients (Cho et al, 2004;Fujimoto et al, 2006;Han et al, 2008;Ishibashi et al, 2004;Newton 2012;Sioka and Kyritsis, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…For example, in the study by Zubizarreta et al (23), 8 (73%) of 11 young NPC patients developed hypothyroidism by follow-up at a median of 63 months. However, Daoud et al (24) reported that 14% of 32 pediatric NPC patients developed hypothyroidism, and Kupeli et al (25) found that 9.5% of 84 patients developed hypothyroidism. The lower incidences of hypothyroidism reported in these studies may be due to limitations in their retrospective designs.…”
Section: Discussionmentioning
confidence: 95%